RESIDENTIAL REAL ESTATE MARKET: ITS ESSENCE AND ROLE IN FINANCIAL-INVESTMENT PROCESSES - Кузнєцова, Анжела; Штейнгауз, Дмитро (Socio-economic relations in the digital society, 2020)
Transformation processes taking place in the financial sector and in the economy in particular, require changes in financial-credit instruments to ensure the effective functioning of the residential real estate market. In the article real estate is considered in five areas of social dimension: social, economic, legal, physical, financial-investment. To better understand the uniqueness of real estate, it is proposed to take into account its essential characteristics from the standpoint of their division into generic (inherent real estate in general)and special (related to the specifics of residential real estate). The classification of housing types on the basis of social and property stratification of the population is presented in the paper. For the residential real estate market, three types of characteristic features (attributes) are defined: generic attributes (related to the affiliation of the residential real estate market to the markets in general), special features (determine its belonging to the real estate market as a separate type of market) and specific features (are individual unique characteristics of the residential real estate market as a special type of real estate market). In a generalized form, the approaches that scientists mostly use to define the concept of «residential real estate market», namely: spatially-determined, mechanistic, neo-institutional, historical-anthropological, structural-systemic, activity, functional, complex. Based on the study of these approaches, in the article own approach to identifying the content of the concept of «residential real estate market» is proposed, based on a logical and structural analysis of concepts, approaches, interpretations and demonstrates the relationship between historical-anthropological, political-economic, neoinstitutional, structural (network), sociocultural concepts with concrete economic and political ideological scientific approaches and the essential elements of identifying the content of the concept of «residential real estate market», which determine its generic differences associated with the essential meaning of the category «market» in general.
Keywords: real estate; essential (generic) features of real estate; specific features of real estate; housing market; residential real estate market; types of housing